2021
DOI: 10.21037/jtd-20-2671
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum, clinical features and diagnosis of chronic cough due to rare causes

Abstract: Background: Chronic cough has many diverse causes, including common and uncommon causes. There are few comprehensive reports on rare causes of chronic cough. The purpose of this study is to determine the etiological distribution, clinical features, and diagnostic value of special examinations in patients with rare causes of chronic cough. Methods: A retrospective analysis of patients with chronic cough who underwent medical history taking, full examination, and etiological treatment over a 13-year period was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Rare causes of chronic cough in adults account for <15% of cases and commonly include protracted bacterial bronchitis, somatic cough syndrome (which is more common in children), diffuse panbronchiolitis and obstructive sleep apnoea syndrome 54 . However, only limited high-quality evidence is available regarding their prevalence and clinical implications in adults with chronic cough.…”
Section: Epidemiologymentioning
confidence: 99%
“…Rare causes of chronic cough in adults account for <15% of cases and commonly include protracted bacterial bronchitis, somatic cough syndrome (which is more common in children), diffuse panbronchiolitis and obstructive sleep apnoea syndrome 54 . However, only limited high-quality evidence is available regarding their prevalence and clinical implications in adults with chronic cough.…”
Section: Epidemiologymentioning
confidence: 99%
“… 1 Many conditions present chronic cough as sole symptom, including cough variant asthma, eosinophilic bronchitis, upper-airway cough syndrome, gastroesophageal reflux cough, 2 , 3 as well as some rare causes like protracted bacterial bronchitis, obstructive sleep apnea syndrome, and vocal cord disfunction. 4 Sometime no pathological causes of cough could be identified even after full investigations or cough still persist after treatment directed to the potential conditions. Those patients are defined as refractory chronic cough or unexplained chronic cough.…”
Section: Introductionmentioning
confidence: 99%
“…Common causes of cough in the preschool age are post-infectious airway infections, airway anomalies, or asthma (32). However, PBB is more common in preschool-aged children and marginally more common in males (33,34). A study (35) that recruited 903 children presenting with acute cough and followed-up for development of chronic cough found that the risk factors for PBB were: childcare attendance [adjusted relative risk (aRR) = 2.32, 95% CI 1.48-3.63], prior history of chronic cough (aRR = 2.63, 95% CI 1.72-4.01), and age <2-years (<12-months: aRR = 4.31, 95% CI 1.42-13.10; 12-<24 months: aRR = 2.00, 95% CI 1.35-2.96).…”
Section: Pre-school Childrenmentioning
confidence: 99%